Bimetallic Mixed Clusters Highly Loaded on Porous 2D Graphdiyne for Hydrogen Energy Conversion. Issue 21 (8th September 2021) - Gao, Yang; Xue, Yurui; Liu, Taifeng; Liu, Yuxin; Zhang, Chao; Xing, Chengyu; He, Feng; Li, Yuliang
Abstract: There is no doubt that hydrogen energy can play significant role in promoting the development and progress of modern society. The utilization of hydrogen energy has developed rapidly, but it is far from the requirement of human. Therefore, it is very urgent to develop methodologies and technologies for efficient hydrogen production, especially high activity and durable electrocatalysts. Here a bimetallic oxide cluster on heterostructure of vanadium ruthenium oxides/graphdiyne (VRuO x /GDY) is reported. The unique acetylene‐rich structure of graphdiyne achieves outstanding characteristics of electrocatalyst: i) controlled preparation of catalysts for achieving multiple‐metal clusters; ii) regulation of catalyst composition and morphology for synthesizing high‐performance catalysts; iii) highly active and durable hydrogen evolution reaction (HER) properties. The optimal porous electrocatalyst (VRu0.027 O x /GDY) can deliver 10 mA cm −2 at low overpotentials of 13 and 12 mV together with robust long‐term stability in alkaline and neutral media, respectively, which are much smaller than Pt/C. The results reveal that the synergism of different components can efficiently facilitate the electron/mass transport properties, reduce the energy barrier, and increase the active site number for high catalytic performances. Abstract : A general method is established to controllably induce bimetallic cluster growth using graphdiyne special structure, realizing the controllable regulation of the catalyst composition and morphology of the bimetallitic mixed clusters. This bimetallic oxide cluster on heterostructures of vanadium‐ruthenium oxides/graphdiyne (VRuO x /GDY) shows highly active and durable hydrogen evolution reaction (HER) performances much better than that of commercial Pt/C.